2010
DOI: 10.1016/j.phytochem.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites of Bagassa guianensis Aubl. wood: A study of the chemotaxonomy of the Moraceae family

Abstract: International audienceIn order to explain the durability of the Moraceae plant family, phytochemistry of Bagassa guianensis was performed. Ethyl acetate extract was obtained from the heartwood and 18 secondary metabolites were isolated, including 6 moracins [6-O-methyl-moracin M, 6-O-methyl-moracin N and moracin Z; previously identified: moracin M, moracin N and moracin P], 8 stilbenoids [presently identified: ( )-epialboctalol and arachidin 4; previously identified: alboctalol, trans-resveratrol, arachidin 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
(54 reference statements)
3
24
0
2
Order By: Relevance
“…Deon et al (1980) reported the same flavonoid (Morin) in Morus mesozygia. Recently other kinds of flavonoids and stilbenoids were identified in Bagassa guianensis, a species from the moraceae family (Royer et al 2010). Interestingly, resorcinol and β-sitosterol, which are reported in this study, were also identified in Bagassa guianensis.…”
Section: Table1 Identified Compounds In the Extractives Of White Mulsupporting
confidence: 65%
“…Deon et al (1980) reported the same flavonoid (Morin) in Morus mesozygia. Recently other kinds of flavonoids and stilbenoids were identified in Bagassa guianensis, a species from the moraceae family (Royer et al 2010). Interestingly, resorcinol and β-sitosterol, which are reported in this study, were also identified in Bagassa guianensis.…”
Section: Table1 Identified Compounds In the Extractives Of White Mulsupporting
confidence: 65%
“…The IR spectrum showed characteristic absorption bands of a hydroxy group (3342 cm À1 ) and a benzene ring (1612 and 1516 cm À1 ). The UV spectrum of 6 was similar to that of alboctalol (9) (Royer et al, 2010). The 1 H NMR spectrum showed one pair of methylene protons at d 2.21 (1H, br s, H ax -6) and 2.42 (1H, dd, J = 15.6, 3.2 Hz, H eq -6), five methine protons at H-11), and 4.93 (1H, br s, H-12).…”
Section: Chemical and Structural Characterization Of Compounds Isolatmentioning
confidence: 67%
“…3. In this proposal, two molecules of oxyresveratrol experienced a [4 + 2] Diels-Alder type reaction to give alboctalol (9) and/or epialboctalol (Royer et al, 2010), which is then followed by a phenolic oxidative de-resorcinol elimination process, forming another ligand (Li et al, 2003) for an additional [4 + 2] reaction that led consequently to the formation of artoxanthol (6). Although the existence of a Diels-Alderase in A. xanthocarpus is still unknown, at least three Diels-Alder type adducts, namely artoxanthol (6), artoxanthochromane (7) , and alboctalol (9), have been identified from this plant and other Moraceous plants (Royer et al, 2010).…”
Section: Chemical and Structural Characterization Of Compounds Isolatmentioning
confidence: 99%
“…Keberadaan tepung murbei walau telah dikukus tetap masih dapat dikenali oleh larva B. mori. Di sini mengandung makna bahwa pengukusan tidak menghilangkan senyawa (metabolit sekunder) yang terdapat pada daun murbei walaupun menu rut Takuya et al (2009) merupakan metabolit sekunder, diantaranya: ber bagai moracin (6 jenis), stilbenoid, quercetin, re sorcinol dan betasitosterol (Zhishen et al, 1999;Royer et al, 2010). Pakan F adalah kombinasi pakan yang 100% formula pakan ayam, tidak mengandung tepung murbei sama sekali, tetapi ditambahkan zat aditif (beta sitosterol).…”
Section: Pembahasanunclassified
“…Pakan inipun masih dimakan oleh larva B. mori, dengan konsumsi sebesar 3,28 g/larva, tidak berbeda nyata dengan konsumsi pa kan larva yang diberi pakan tepung murbei sebesar 3,36 g/larva (perlakuan A). Beta sitosterol adalah salah satu komponen kimia yang terdapat dalam daun murbei (Royer et al, 2010). Ini berarti bahwa larva ulat sutera Bombyx mori tidak harus mema kan daun murbei, asal ada salah satu molekul me tabolit sekunder yang ada di dalam daun murbei yang ditambahkan ke dalam pakan tersebut.…”
Section: Pembahasanunclassified